1984
DOI: 10.1111/j.1471-4159.1984.tb12740.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Neurotrophic Regulation of Collagen‐Tailed Acetylcholinesterase in Immature Skeletal Muscle by β‐Endorphin

Abstract: Acetylcholinesterase (AChE) was extracted in a high-saline medium from gastrocnemius muscles of rat embryos and young rats aged 14 days' gestation to 40 days post partum. The molecular forms of the enzyme were separated by low-salt precipitation, followed by velocity sedimentation. During gestation, all molecular forms increased in activity, particularly the 16 S (A12) form. During the first 2 weeks of life, there was a large increase in the activity of soluble AChE (G forms), whilst the activity of insoluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Haynes et al (11) showed recently that ,B-endorphin inhibits the formation of A12 AcChoEase from smaller aggregates in cultured immature rat muscle. On the other hand, the dipeptide glycyl-L-glutamine (Gly-Gln), which is formed by endopeptidase cleavage of the terminal of P-endorphin (12), was found by Haynes and Smith (13) to enhance markedly the formation of A12 and G4 AcChoEase in cultured embryonic rat and chicken skeletal muscle.…”
mentioning
confidence: 99%
“…Haynes et al (11) showed recently that ,B-endorphin inhibits the formation of A12 AcChoEase from smaller aggregates in cultured immature rat muscle. On the other hand, the dipeptide glycyl-L-glutamine (Gly-Gln), which is formed by endopeptidase cleavage of the terminal of P-endorphin (12), was found by Haynes and Smith (13) to enhance markedly the formation of A12 and G4 AcChoEase in cultured embryonic rat and chicken skeletal muscle.…”
mentioning
confidence: 99%
“…Both enkephalins and (3-endorphin (13-EP) have been localized to immature neurons in germinal layers of the perinatal rat brain and spinal cord (Loughlin et al, 1985;Zagon et al, 1985). 13-Endorphin is observed later in postnatal development in spinal a-motoneurons, together with several other neuropeptides (Haynes et al, 1982(Haynes et al, , 1986Villar et al, 1988), where there is now strong evidence for their role in the transsynaptic trophic regulation of postsynaptic chemosensitivity at the nerve-muscle synapse (Haynes et al, 1984;Villar et al, 1989). Whereas enkephalins continue to be expressed in neurons throughout the adult brain, the amount of (3-EP and its derivatives in several parts of the central nervous system undergoes a decrease in postnatal times (Bayon et al, 1979) when its biosynthesis becomes limited to the hypothalamus and a small number of other discrete sites (Elkabes et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In normal adults very few motor nerves were immunoreactive but there was a significantly higher proportion of immunoreactive nerves in adult mice with muscular dystrophy (Haynes & Smith, 1985;Hughes & Smith, 1988) or motoneurone disease (Hughes & Smith, 1989). It has been shown that /-endorphin increases the responses of isolated skeletal muscles to acetylcholine (Haynes et al 1983) and it may also promote aspects of synaptogenesis at the neuromuscular junction (Haynes et al 1984). It seemed possible that the peptide acts on the muscle membrane via specific receptors and in the present study we have used autoradiography to investigate the presence of specific binding sites for this peptide in murine skeletal muscles.…”
Section: Pmentioning
confidence: 99%